Integrating Thinking Styles into Differentiated Instruction: Enhancing Learning Outcomes in Science Education - Muhammad Jarnawi; Haeruddin Haeruddin; I Komang Werdhiana; Syamsuriwal Syamsuriwal; Siti Eneng Sururiyatul Mu’aziyah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research aims to advance science education by integrating Gregorc’s Thinking Style Model into differentiated instruction, thereby accommodating students’ diverse cognitive needs and improving their academic performance and learning outcomes in science education. Methodology: This study employed a quasi-experimental design conducted at MTs Al-Khairaat Bora, involving 70 students (36 male and 34 female). Thinking styles were identified using the Gregorc Thinking Style Inventory. Differentiated learning modules were developed and implemented, supported by pre-test and post-test assessments, classroom observations, and feedback surveys analyzed quantitatively and qualitatively. Main Findings: This study investigated the distribution of cognitive styles among 70 students, finding that Abstract Random (30.22%) and Concrete Random (28.30%) were the most predominant, followed by Abstract Sequential (16.48%) and Concrete Sequential (11.54%). Instruction tailored to these cognitive styles resulted in an increase in post-test scores for the experimental group (from 65 to 85), surpassing the control group (from 64 to 70). Novelty/Originality of this study: This study integrates Gregorc’s Thinking Style Model with differentiated instruction, offering a novel approach to adapting science education. By identifying students' thinking styles, it enhances engagement and understanding, aligning teaching methods with cognitive preferences. The study contributes to improving educational practices by fostering better learning outcomes for diverse student groups.